Strategi Pemasaran Dalam Meningkatkan Daya Tarik Tamu di Grand Bunda Hotel Syariah - Latifa Sri Oktavia; Harry Yulianda (i-Tourism: Jurnal Pariwisata Syariah, 2021)
The purpose of this study is to describe the marketing management in the Grand Bunda Hotel Syariah based on the marketing mix (product, price, place, promotion) and see the marketing strategy through the marketing mix that needs to be done by the Bunda hotel in increasing consumer attractiveness.This type of research is descriptive qualitative by conducting research and direct interviews to determine the marketing strategy through the marketing mix of product, price, place, promotion at Grand Bunda Hotel Syariah Bukittinggi. Data collection techniques through interviews and documentation. The data analysis technique is using data reduction analysis stages, which is a form of analysis that sharpens and shows important things in the results of interviews, data presentation provides conclusions from the results of interviews that have been compiled which allows drawing conclusions and taking action, and finally drawing conclusions. This is the most important and final process carried out in research to get a conclusion that can be verified based on the presentation of data obtained from sources.From the research that the author did in the field, it can be concluded that the marketing strategy used by Grand Bunda Hotel Syariah is a product strategy that provides the facilities needed by guests such as a place for ablution, Qibla direction and prayer equipment. The price strategy offered is affordable for all people by determining economic prices. Its location strategy is very strategic by being near the tourist attraction of Bukittinggi. The promotional strategy is carried out by giving brochures to every guest who visits there and sales promotions carried out during meeting visits to other places. And the strategy that Grand Bunda Hotel Syariah did not do was a potential product strategy by maximizing social media, using influencer services, creating blogs about hotels. Additional product strategies such as providing a Muslim-inspired swimming pool and a Muslim-inspired SPA with a separate place for men and women.